DETERMINATION OF THE SATELLITE’S ROTATION USING ITS LIGHT CURVE - Pavlenko, Daniil (Одеські астрономічні публікації, 2013)
This article describes the method of determination of the Earth’s artificial satellite’s free (unplanned) rotation using its light curve and preliminary computed brightness charts (the spatial indicatrices of light scattering by the artificial satellite’s surface), as well as provides examples of such solutions for simulated occurrences